Obinutuzumab-Induced Inﬂammatory Bowel Disease-Like Pancolitis: A First Case Report - Mendes,Raquel R. (2024)
Abstract Introduction: Obinutuzumab is a type II anti-CD20 monoclonal antibody associated with a higher rate of toxicity when compared to rituximab. Gastrointestinal side-effects have been reported but data is still sparse. Case Presentation: A 47-year-old female with medical history of stage IV follicular non-Hodgkin lymphoma under chemotherapy presented with chronic bloody diarrhea and iron deﬁciency anemia. Endoscopic and histologic features resembled inﬂammatory bowel dis-ease (IBD), imposing a thorough differential diagnosis. The diagnosis of obinutuzumab-induced pancolitis was made and the drug was suspended with subsequent clinical improvement. Conclusion: This is the ﬁrst case report of obinutuzumab-induced pancolitis. The challenging differential diagnosis of IBD required a multi-disciplinary approach with subsequent outcome and management implications.